The natural history of phytosterolemia: Observations on its homeostasis. (February 2018) - Mymin, David; Salen, Gerald; Triggs-Raine, Barbara; Waggoner, Darrel J.; Dembinski, Thomas; Hatch, Grant M.
Abstract: Background and aims: Phytosterolemia is a rare genetic disease caused by mutation of the ABCG5/8 gene. Our aim was to elucidate the natural history and homeostasis of phytosterolemia. Methods: We analyzed a Hutterite kindred consisting of 21 homozygotes with phytosterolemia assembled over a period of two decades, all of whom carried the ABCG8 S107X mutation and were treated with ezetimibe. Results: Most of these subjects were asymptomatic and devoid of clinical stigmata, and this, since they were ascertained primarily by a process of cascade testing, suggests that, relative to its true prevalence, phytosterolemia is a condition of low morbidity. All subjects have responded well to treatment with ezetimibe. Initial (pre-treatment) and post-ezetimibe levels of cholesterol and sitosterol were measured and percentage changes on ezetimibe were calculated. We found initial levels to be inversely related to subjects' ages as were percentage responses to ezetimibe therapy. There was also a direct correlation between initial levels and percentage responses to ezetimibe. Hence on-treatment levels were very uniform. Conclusions: This evidence of a link with age leads us to propose that an age-related change in cholesterol and sterol homeostasis occurs at puberty in phytosterolemia and that the change is due to high sterol and/or stanol levels causing feedback inhibition of sterol regulatory element-binding protein (SREBP-2) processing. This would explain the well-documented phenomenon of depressed cholesterol synthesis in phytosterolemia. It is also well-known that LDL-receptor activity is increased, and this feasibly explains reduced LDL levels and consequent reduction of plasma cholesterol and sitosterol levels. Downregulated SREBP-2 processing would be expected to also lower proprotein convertase subtilisin/kexin type 9 (PCSK9) levels and this would explain high LDL-receptor activity. The above state could be termed disrupted homeostasis and the alternative, seen mostly in children and characterized by hypercholesterolemia and hypersterolemia, simple homeostasis.